α-Amylase and α-Glucosidase Inhibitory Saponins from Polyscias fruticosa Leaves - Tran Thi Hong Hanh; Nguyen Hai Dang; Nguyen Tien Dat (Journal of Chemistry)
Three bisdesmosidic saponins 3-O-[β-D-glucopyranosyl-(1→4)-β-D-glucuronopyranosyl] oleanolic acid 28-O-β-D-glucopyranosyl ester (1), polyscioside D (2), and 3-O-{β-D-glucopyranosyl-(1→2)-[β-D-glucopyranosyl-(1→4)]-β-D-glucuronopyranosyl} oleanolic acid 28-O-β-D-glucopyranosyl-(1→2)-β-D-galactopyranosyl ester (3) were isolated from a methanol extract of Polyscias fruticosa (L.) Harms leaves. Compound 1 was obtained as a main constituent and compound 3 was reported for the first time and named as polyscioside I. Saponin 1 inhibited porcine pancreas α-amylase and yeast α-glucosidase activities while 2 and 3 were inactive. Synergistic inhibitory effect on α-amylase was observed from the combination of low concentrations of 1 and acarbose. The findings suggest the use of P. fruticosa and its major saponin 1 for the prevention and treatment of diabetes and its complications.